(3GdMOGFbs - (3jhSa Hf CMeO Hf EHQGgje GdOQGRj GdHMQGfj, GHf oYrUoahQ,J (B1186 (3g` s
(3ChdgG (B:s
(3GeG HYO ajbhd jhSa Hf CMeO s
(3BNQgG (B:s
(3hfbdg ai GdeYJHQ Yf HYV Cgd hef GdCNHGQ GdOGdI Ydi Pdc s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B215 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B268s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3CUhd Gdabgs